The Frequency of Fibromyalgia and its Relationship With Disease Activity in Female Patients With Behçet’s Disease: A Cross Sectional Study - Koray AYAR,; Burcu METİN ÖKMEN,; Lale ALTAN,; Esra KÖSEGİL ÖZTÜRK, (Archives of Rheumatology, 2020)
Objectives: This study aims to determine the incidence of fibromyalgia (FM) in female patients with Behçet's disease (BD) and to investigate whether disease activity changes in the presence of FM in female patients with BD. Patients and methods: This cross-sectional study included 72 female patients with BD (mean age 39.7±10.5 years; range, 22 to 74 years) between June 2018 and February 2019. The frequency of FM was evaluated according to the American College of Rheumatology alternative criteria. Active clinical features and BD activity were evaluated with the Behçet's disease activity form (BDCAF). Results: The prevalence of FM was 29.2% in the BD patients. BD clinical activity index, patients’ perceptions of disease activity and clinicians' overall perceptions of disease activity scores were significantly higher in BD patients with FM (p=0.003, p<0.001 and p=0.025, respectively). The active clinical features of BD were not different between the groups except for genital ulcer. The prevalence of active genital ulcers was higher in BD patients with FM than in BD patients without FM (38.1% vs. 13.7%, respectively). Conclusion: Disease activity is higher in female BD patients with FM than those without FM. High disease activity in female BD patients with FM may be associated with the presence of genital ulcers.